2018
DOI: 10.1002/joc.5924
|View full text |Cite
|
Sign up to set email alerts
|

The water cycle of the mid‐Holocene West African monsoon: The role of vegetation and dust emission changes

Abstract: During the mid-Holocene (6 kyr BP), West Africa experienced a much stronger and geographically extensive monsoon than in the present day. Changes in orbital forcing, vegetation and dust emissions from the Sahara have been identified as key factors driving this intensification. Here, we analyse how the timing, origin and convergence of moisture fluxes contributing to the monsoonal precipitation change under a range of scenarios: orbital forcing only; orbital and vegetation forcings (Green Sahara); orbital, vege… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 67 publications
4
28
0
Order By: Relevance
“…Using a model that only resolves direct aerosol effects, Pausata et al (2016) accounted for changes in MH vegetation cover and the associated dust reduction and found that a reduced dust load enhanced local rainfall by as much as 2.5 mm/day over the Sahara and shifted the West African Monsoon (WAM) northward. With the same model, Messori et al (2018) showed that increased moisture recycling was a key driver of the rainfall response to reduced atmospheric dust load. However, the potential role of indirect aerosol effects, which have at least equal global radiative forcing (Myhre et al, 2013), on AHP precipitation, have never been explored.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Using a model that only resolves direct aerosol effects, Pausata et al (2016) accounted for changes in MH vegetation cover and the associated dust reduction and found that a reduced dust load enhanced local rainfall by as much as 2.5 mm/day over the Sahara and shifted the West African Monsoon (WAM) northward. With the same model, Messori et al (2018) showed that increased moisture recycling was a key driver of the rainfall response to reduced atmospheric dust load. However, the potential role of indirect aerosol effects, which have at least equal global radiative forcing (Myhre et al, 2013), on AHP precipitation, have never been explored.…”
Section: Introductionmentioning
confidence: 99%
“…To date, most model simulations, including those from Paleoclimate Modelling Intercomparison Project Phase 3, specify preindustrial (PI) dust loading (Braconnot et al, 2011;Taylor et al, 2012). With the same model, Messori et al (2018) showed that increased moisture recycling was a key driver of the rainfall response to reduced atmospheric dust load. With the same model, Messori et al (2018) showed that increased moisture recycling was a key driver of the rainfall response to reduced atmospheric dust load.…”
Section: Introductionmentioning
confidence: 99%
“…Kutzbach et al, 1996;Kutzbach and Liu, 1997;Claussen and Gayler, 1997). More recent modelling efforts have confirmed this, and have further highlighted the potential role of an incorrect representation of atmospheric aerosols in favouring the dry bias (Pausata et al, 2016;Gaetani et al, 2017;Messori et al, 2019). Such hypothesis has triggered a lively discussion in the literature (cf.…”
Section: The Mid-holocene Green Sahara: Background and Datamentioning
confidence: 95%
“…and could be implemented as an additional sensitivity experiment when available. Changes in atmospheric dust loading are not included in the past1000 simulation but are important during the earlier part of the Holocene (Pausata et al, 2016;Tierney et al, 2017;Messori et al, 2019). Although continuous reconstructions of dust loading through the Holocene are not available, it would be possible to use estimates for particular time-slices (Egerer et al, 2018) to test the sensitivity to this forcing.…”
Section: Implementation Of Lulc In Earth System Model Simulationsmentioning
confidence: 99%